Awareness and perception of cervical cancer among Pre-primary school teachers in Dehradun: A Cross-Sectional study - Das, Monojit; Dobhal, Priyanka; Roy, Debabrata; Rana, Medhavi (Indian Journal of Community Health, 2025)
Background: Cervical cancer is preventable through primary, secondary, and tertiary activities, including health education, HPV vaccination, and early screening. Despite high costs and healthcare barriers, it remains a major public health issue in India. This study assesses knowledge, awareness, and perceptions of pre-primary school teachers in Dehradun about cervical cancer and vaccination. Objectives: To evaluate awareness of cervical cancer, its causes, symptoms, protection, and influencing socio-demographic factors among female teachers. Methods: A 2-month cross-sectional study used a pretested questionnaire on knowledge, attitudes, practices, and socio-demographics among female teachers in Dehradun. Data were analysed with SPSS v21 and Chi-square tests. Results: Of 104 teachers from 23 schools, 47% had heard of cervical cancer, mainly online (86%). About 80% were unaware of risk factors, and 70% didn't know the symptoms. Only 25% knew of vaccination, and none had received it. Twenty percent identified Pap smear as a screening test, with fewer than 3% having undergone it. Significant associations were found between risk factors and awareness of risk factors or warning signs. Conclusion: Raising awareness, education, and communication are vital for screening and prevention. Even educated women in Dehradun lack adequate knowledge of prevention, highlighting the need for increased health awareness.